A Novel RFID Sensing System Using Enhanced Surface Wave Technology for Battery Exchange Stations. (30th September 2014) - Lai, Yeong-Lin; Chang, Li-Chih; Liu, Tai-Hwa; Sung, Yi-Chun; Yin, Cheng-Lun
Abstract : This paper presents a novel radio-frequency identification (RFID) sensing system using enhanced surface wave technology for battery exchange stations (BESs) of electric motorcycles. Ultrahigh-frequency (UHF) RFID technology is utilized to automatically track and manage battery and user information without manual operation. The system includes readers, enhanced surface wave leaky cable antennas (ESWLCAs), coupling cable lines (CCLs), and small radiation patches (SRPs). The RFID sensing system overcomes the electromagnetic interference in the metallic environment of a BES cabinet. The developed RFID sensing system can effectively increase the efficiency of BES operation and promote the development of electric vehicles which solve the problem of air pollution as well as protect the environment of the Earth.